2008
DOI: 10.1186/1479-5868-5-36
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity across the curriculum: year one process evaluation results

Abstract: Background: Physical Activity Across the Curriculum (PAAC) is a 3-year elementary school-based intervention to determine if increased amounts of moderate intensity physical activity performed in the classroom will diminish gains in body mass index (BMI). It is a cluster-randomized, controlled trial, involving 4905 children (2505 intervention, 2400 control).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 25 publications
5
90
0
8
Order By: Relevance
“…The barriers and facilitators documented during the HEALTHY study are similar to those reported in similar school-based intervention studies promoting physical activity and/or nutrition, including Lifestyle Education for Activity Program (LEAP), Middle-School Physical Activity and Nutrition (M-SPAN), Pathways, Peers Running Organized Play (PROPS), Physical Activity Across the Curriculum (PAAC), and Trial of Activity for Adolescent Girls (TAAG) [18][19][20][21][22][23][24][25]. Common facilitators reported include interest and support from various school members (i.e., school board member, school administrators, school office staff, teachers, students, and parents), schools that had made physical activity and nutrition a priority prior to study, schools already implementing practices and strategies similar to intervention components, teachers collaborating with one another during implementation, and teachers and food service staff who were motivated and actively engaged in intervention implementation [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…The barriers and facilitators documented during the HEALTHY study are similar to those reported in similar school-based intervention studies promoting physical activity and/or nutrition, including Lifestyle Education for Activity Program (LEAP), Middle-School Physical Activity and Nutrition (M-SPAN), Pathways, Peers Running Organized Play (PROPS), Physical Activity Across the Curriculum (PAAC), and Trial of Activity for Adolescent Girls (TAAG) [18][19][20][21][22][23][24][25]. Common facilitators reported include interest and support from various school members (i.e., school board member, school administrators, school office staff, teachers, students, and parents), schools that had made physical activity and nutrition a priority prior to study, schools already implementing practices and strategies similar to intervention components, teachers collaborating with one another during implementation, and teachers and food service staff who were motivated and actively engaged in intervention implementation [18][19][20][21][22].…”
Section: Discussionmentioning
confidence: 60%
“…These barriers include financial constraints in the school food service system, inadequate facility space to implement activities or store equipment, lack of school personnel to deliver intervention components, and faculty and staff turnover [18][19][20][22][23][24]. Other barriers related to logistical issues in terms of food and beverage ordering problems, school districts with highly centralized food service systems impeding individual school nutrition changes, school scheduling problems, and teacher time constraints [18][19][20][22][23][24][25]. Some teachers reported being unable to implement intervention components due to school prioritization of nonhealth-related curricula and standardized testing requirements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not to say that a process evaluation should be conducted in lieu of testing for an effect, nor that the process evaluation will fully explain why this initial HPSS model did not have a significant impact on behavior, but rather turning to the process data at this point may shed light on what aspects of the intervention were well received and executed and where improvements can be made. "Process evaluations are not a miracle ingredient", but can be an effective way to map progress made during a school-based intervention in terms of curriculum changes, knowledge development, quality assurance, and enjoyment [69,70]. Alternately, since uptake was slower than anticipated, it may be that additional time was needed for the program to be adopted sufficiently to impact student behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have targeted teachers' perceptions of their use of physical activity (Cothran, Hodges-Kulinna, & Garn, 2010;Dinkel, Schaffer, Snyder, & Lee, 2017;Gately, Curtis, & Hardaker, 2013;Gibson et al, 2008;Howie, NewmanNorlund, & Pate, 2014;Maeda & Murata, 2004;Martin & Murtagh, 2015;McMullen, Kulinna & Cothran, 2014;Stylianou, Hodges-Kulinna, & Naiman, 2016). However, few studies have been done on teachers who self-initiate regular physical activity in their classrooms-independent of a specific program or study that is aimed to increase student activity levels.…”
Section: Physical Activity and School Performancementioning
confidence: 99%